Service Quality in Halal Tourism and Perceived Value as Determinants of Satisfaction and Revisit Intention among Muslim Travelers - Nurhasanah, Dila Padila; Nasution, Edwin Sugesti; Chandra, Johnny; Moktar, Brilian; Harja, Ngiw Aman (West Science Islamic Studies, 2026)
This study investigates the influence of service quality in halal tourism and perceived value on tourist satisfaction and revisit intention among Muslim tourists in Indonesia. A quantitative approach was employed using data collected from 150 respondents through a structured questionnaire based on a Likert scale. The data were analyzed using SmartPLS 3 to evaluate both the measurement and structural models. The results indicate that service quality has a significant positive effect on perceived value and tourist satisfaction. Perceived value also significantly influences satisfaction and revisit intention. Furthermore, tourist satisfaction is found to have the strongest effect on revisit intention and plays a significant mediating role in the relationship between service quality, perceived value, and revisit intention. These findings highlight the importance of delivering high-quality, halal-compliant services that enhance perceived value and satisfaction, ultimately strengthening tourist loyalty. This study contributes to the halal tourism literature by providing empirical evidence on the integrated relationships among key variables and offers practical insights for improving the competitiveness of Indonesia’s halal tourism sector.